Impact of Aspirin Intake on Postoperative Survival after Primary Pancreatic Resection of Pancreatic Ductal Adenocarcinoma—A Single-Center Evaluation - Hackner, Danilo; Hobbs, Mirianna; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Biomedicines, 2023)
(1) Background: The intake of aspirin (ASS) has been demonstrated to have a relevant impact on the pathogenesis, incidence and outcome in different solid gastrointestinal tumors. However, data on the effect of ASS on the short-term outcome and the long-term survival in patients with pancreatic carcinoma are still limited. (2) Methods: A total of 213 patients who underwent primary resection of PDAC at the University Hospital of Erlangen from January 2000 to December 2018 were included in this retrospective single-center study in total. Patients were stratified according to the aspirin intake into three groups: continuous aspirin intake (cASS), perioperatively interrupted aspirin intake (iASS) and no aspirin intake (no ASS) at the timepoint of surgery. The postoperative outcome as well as long-term survival were compared between the groups. (3) Results: There were no differences regarding postoperative morbidity (iASS: 54% vs. cASS: 53% vs. no ASS: 64%, p = 0.448) and in-hospital mortality (iASS: 4% vs. cASS: 10% vs. no ASS: 3%, p = 0.198) between the groups. The overall survival (OS) and disease-free survival (DFS) did not differ in the groups when comparing the ASS-intake status (OS: iASS 17.8 months vs. cASS 19.6 months vs. no ASS 21.6 months, p = 0.489; DFS: iASS 14.0 months vs. cASS 18.3 months vs. no ASS 14.7 months, p = 0.957). Multivariate analysis revealed that age (hazard ratio (HR) 2.2, p < 0.001), lymph node-positive status (HR 2.0, p < 0.001), R status 1 or 2 (HR 2.8, p < 0.001) and differentiation with a grading of 3 (HR 1.7, p = 0.005) were significant independent prognostic factors regarding the OS. Moreover, age (HR 1.5, p = 0.040), lymph node-positive status (HR 1.8, p = 0.002) and high-grade (G3) carcinomas (HR 1.5, p = 0.037) could be identified as independent prognostic parameters for DFS. (4) Conclusions: In patients undergoing primary surgery for curative resection of pancreatic carcinoma, the perioperative intake of ASS had no significant impact on postoperative outcome, overall and disease-free survival.
CRIS-Team Scopus Importer:2023-06-09
Keywords: aspirin intake; disease-free survival; overall survival; pancreatic ductal adenocarcinoma; pancreatic resection

Impact of Patient Age on Postoperative Short-Term and Long-Term Outcome after Pancreatic Resection of Pancreatic Ductal Adenocarcinoma - Hackner, Danilo; Hobbs, Mirianna; Merkel, Susanne; Siepmann, Timo; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2022)
Simple Summary Pancreatic ductal adenocarcinoma (PDAC) is frequently seen in elderly patients. The aim of our retrospective study was to evaluate the impact of age on postoperative short-term and long-term outcomes in patients undergoing curative pancreatic resection for PDAC. Our data confirm that pancreatic resections can be performed with equal short-term outcomes even in older age. However, patient age significantly influenced the overall and disease-free survival of patients with PDAC undergoing primary resection in curative intent. Therefore, the choice of the optimal therapy concept for each patient should be individualized taking into account the patient's age. (1) Purpose: to evaluate the impact of age on postoperative short-term and long-term outcomes in patients undergoing curative pancreatic resection for PDAC. (2) Methods: This retrospective single-center study comprised 213 patients who had undergone primary resection of PDAC from January 2000 to December 2018 at the University Hospital of Erlangen, Germany. Patients were stratified according the age into two groups: younger (<= 70 years) and older (>70 years) patients. Postoperative outcome and long-term survival were compared between the groups. (3) Results: There were no significant differences regarding inhospital morbidity (58% vs. 67%, p = 0.255) or inhospital mortality (2% vs. 7%, p = 0.073) between the two groups. The median overall survival (OS) and disease-free survival (DFS) were significantly shorter in elderly patients (OS: 29.2 vs. 17.1 months, p < 0.001, respectively; DFS: 14.9 vs. 10.4 months, p = 0.034). Multivariate analysis revealed that age was a significant independent prognostic predictor for OS and DFS (HR 2.23, 95% CI 1.58-3.15; p < 0.001 for OS and HR 1.62, 95% CI 1.17-2.24; p = 0.004 for DFS). (4) Conclusion: patient age significantly influenced overall and disease-free survival in patients with PDAC undergoing primary resection in curative intent.
CRIS-Team WoS Importer:2022-09-09

Time to Surgery Does Not Affect Overall or Disease-Free Survival of Patients with Primary Resectable PDAC - Jacobsen, Anne; Hobbs, Mirianna; Merkel, Susanne; Mittelstädt, Anke; Czubayko, Franziska; Krautz, Christian; Grützmann, Robert; Brunner, Maximilian; Weber, Georg (Journal of Clinical Medicine, 2022)
(1) Background: Delay in therapy for pancreatic ductal adenocarcinoma (PDAC) may contribute to a worse outcome. The aim of this study was to investigate the prognostic value of time from diagnosis to surgery in patients undergoing upfront surgery for primarily resectable pancreatic carcinoma. (2) Methods: This retrospective single-center study included 214 patients who underwent primary resection of PDAC from January 2000 to December 2018 at University Hospital Erlangen. Using a minimum p-value approach, patients were stratified according to time to surgery (TtS) into two groups: TtS <= 23 days and TtS > 23 days. Postoperative outcome and long-term survival were compared. (3) Results: Median TtS was 25 days. The best cut-off for TtS was determined as 23 days. There were no differences regarding postoperative outcome or overall survival (OS) and disease-free survival (DFS) (OS: 23.8 vs. 20.4 months, p = 0.210, respectively, and DFS: 15.8 vs. 13.6 months, p = 0.187). Multivariate analysis revealed age, lymph node metastasis, tumor differentiation and resection status as significant independent prognostic predictors for OS and DFS. (4) Conclusions: A delay of surgery > 23 days after first diagnosis does not affect overall or disease-free survival of patients with primary resectable PDAC. However, the psychological impact of a delay to patients waiting for surgery should not be underestimated.
CRIS-Team WoS Importer:2022-08-26